Retaining a diverse workforce: the impact of gender‐focused human resource management. (30th June 2015) - Ali, Muhammad; Metz, Isabel; Kulik, Carol T.
Abstract : Demography theory suggests that high gender diversity leads to high turnover. As turnover is costly, we tested the following: a main effect prediction derived from demography theory, and a moderating effect prediction derived from the relational framework. Data on 198 publicly listed organisations were collected through a human resources decision‐maker survey and archival databases. The results indicate that higher gender diversity leads to lower turnover in organisations with many gender‐focused policies and practices. Findings suggest that organisations can lower their turnover rates by increasing their gender diversity and by implementing gender‐focused policies and practices.